In vitro antidiabetic property and phytochemical profiling of Mangifera odorata pulp using UHPLC-ESI-Orbitrap-MS/MS - Lasano, Nur Fatimah; Ramli, Nurul Shazini; Abdul Hamid, Azizah; Karim, Roselina; Pak Dek, Mohd Sabri; Abas, Faridah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2021)
Mangifera odorata, or known as “kuini” in Malay, is considered an underutilised climacteric tropical fruit. Recent studies had suggested that the by-products of M. odorata may serve as functional food ingredients based on their nutritional values and biological activities. Thus, the present work was aimed to determine the nutritional composition, antidiabetic properties through α-glucosidase and α-amylase inhibition assays, and phytochemical profiling of M. odorata pulp using ultra-high-performance liquid chromatography-electrospray ionisation orbitrap tandem mass spectrometry (UHPLC-ESI-Orbitrap-MS/MS). Proximate analyses found that M. odorata pulp contained high amounts of soluble fibre and moisture. The main sugar in the pulp was identified as sucrose, while ß-carotene, potassium, calcium, iron, and zinc were the major vitamins and minerals. The extraction of the sample in water, acetone, methanol, and ethanol were performed for the determination of antidiabetic assay. The results showed that 60% of ethanolic extract had the highest α-amylase inhibitory activity among the four extraction solvents. The findings revealed high levels of mangiferin in the active extract, which may be responsible for the α-amylase inhibition activity, thus contributing to lower post-prandial blood glucose. The present work provides evidence on the nutritional benefits of M. odorata pulp, as well as the potential use of its ethanolic extract as an α-amylase inhibitor.